Effect of exhaust gas recirculation on a CRDI engine fueled with waste plastic oil blend. (1st September 2018) - Ayodhya, Archit S.; Lamani, Venkatesh T.; Bedar, Parashuram; Kumar, G.N.
Abstract: The inevitable rise in the usage of plastic poses a serious threat to the environment owing to their non-biodegradable nature. The lack of proper infrastructure for treating and recycling plastic wastes give rise to the disposal problem. However, the oil synthesized from these waste plastics can be used as an alternative fuel for C.I engines which not only helps to tackle the disposal problem but also aids in recovering precious energy from these wastes. This experimental investigation aims to study the effects of plastic-diesel blend(P30) fuel on the performance, emission and combustion characteristics of a twin cylinder CRDI engine operating at different EGR rates (0%, 10% & 20%). The experimental results showed a slight drop in the engine performance while operating with plastic blend, mainly overall due to its higher viscosity and lower heating value. The vast upsurge of NOX emissions with plastic blend was mitigated by the aid of EGR methodology. Marginal increase in the discharge of regulated emissions like HC, CO and soot were noticed for both plastic blend as well as EGR operations. The experiments were carried out for five different loading conditions varying from 0% to 80% in steps of 20% each and found out that waste plastic-diesel blend can be successfully used as an alternative fuel in diesel vehicles without any prior modifications in the engine.